Muros do Mediterrâneo: Notas sobre a construção de barreiras nas fronteiras de Ceuta e Melilla - Patrick Figueiredo (Cadernos de Estudos Africanos)
There are many material cases that shape the frontiers between E.U. and Africa that deserve attention. I will consider some theoretical approaches to the fences that are being built in the territorial boundaries between Ceuta and Melilla’s enclaves, distancing the European continent from the Moroccan territory, and thus, from Africa. This tendency to separate nation-states with walls can be observed in every continent. Despite commercial liberalization and an increasing flow of political speeches that appeal to the freedom of circulation, developed countries are also engaged in this movement of barrier proliferation that checks and controls the circulation of social agents. To better understand the concepts underlying these fences, I seek to insert them in the constellation of security apparatus that shape our late modernity.